Teacher continuing professional development and team-working competences: A case study from Italy - Chiara Urbani (International Journal for Research in Vocational Education and Training (IJRVET), 2020)
Context: European policies describe the key role of teachers' Vocational Education and Training (VET) in improving students' learning outcomes. In order to improve teacher education, Organisation for Economic Co-Operation and Development (OECD) policies identify competency models as the main framework for understanding teacher professionalism and designing VET policies. By reinterpreting these models through the capability approach, this article aims to identify more relevant competences of preschool teachers in the public and private services of northern and central Italy. Methods: The research began with a comparative analysis of VET policies for preschool teachers to outline more common competences used to define their professional profile. This led to the creation of a new, re-thought competency model used to design a quantitative survey to describe teachers' competences in preschool settings. The self-assessment questionnaire was built on the following competence areas: Management of educational and relational processes, teamwork and large-scale teamwork, networking and governance. The self-assessment questionnaire evaluated 65 preschool teachers' pre-acquired competences and development levels and those more desirable for the future (called "ideal" co.). The comparison of areas and their values reveals critical results, particularly related to teamwork competences at different levels. Results: The study outlines the structure of preschool teacher professionalism based on "traditional" competences (e.g., educational relationships with children) and some "innovative" competences (e.g., networking and governance), which appeared to be more desirable in teachers' evaluations. However, the comparison of the data reveals that governance competences are better evaluated then teamwork co., introducing some hypotheses about the quality of relationships in the community of practice. Conclusions: The research outlines how the competences emerging as relevant for teachers need to be better activated in professional settings to become strategically important. The results related to teamwork and governance competences focus on the importance of informal and extended learning contexts to teachers' socio-relational competence development. The organization of the school system needs to be re-thought and extracurricular competences need to increase to foster the generative development of informal learning communities at intra- and extra-school levels. According to the capability approach, the research reveals the extreme complexity of preschool teacher professionalism. For vocational education and training, its underlines the re-thinking of the preschool teacher profile as a co-designer of learning environments, which includes building formal and informal competences to foster communities of practice as a learning and generative process.
urn:nbn:de:gbv:18-10-3029
Keywords: 330; Teacher Professional Development; Teacher Education; Teacher Training; Preschool Teacher; Competency Model; Agency; Vocational Education and Training; VET